ANALISIS PUTUSAN NOMOR 24/PID.PRA/2018/PN.JKT. SEL TENTANG PUTUSAN HAKIM MENGENAI PENETAPAN STATUS TERSANGKA BARU DI PRAPERADILAN - Vika Anggraini; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Pretrial is a judicial institution that only has authority limited to deciding whether the arrest or detention is valid or not, termination of the investigation, termination of prosecution, including compensation or rehabilitation for someone whose case has been terminated. But in judge Effendi Mukhtar decision as a single judge in a pretrial case Number 24 / Pid.Pra / 2018 / PN.Jkt.Sel dropped a verdict in which one of the contents stated "Establishing a suspect against Boediono, Muliaman D Hadad, Raden Pardede and others". The decision was deemed unusual because the order to determine the suspect did not include pre-trial competencies which had been valid and considered to be beyond authority because the determination of the suspect was the authority of the investigator after the minimum evidence was met, as well as the suitability of the alleged offense. The purpose of this thesis, namely: First, to determine the authority of the judge in deciding the determination of the status of a new suspect in pretrial. Second, to find out the basic reconstruction of judges' consideration in the decision to better accommodate the legal values and sense of justice that lives in the community.This type of research can be classified as normative, research conducted by examining secondary legal material or research based on the standard rules that have been recorded is also called library research.Based on the results of the study, two things can be concluded. First, even though judges may be progressive, they certainly must not violate criminal procedural law, in this case, the pretrial procedural law. Determination of a suspect is absolutely the authority of the investigator, so it should be for the sake of legal certainty, the judge cannot give the verdict as in the pretrial decision number 24 / Pid.Pra / 2018 / PN.Jkt.Sel. Second, the construction of judicial legal considerations is closely related to how judges behave. The attitude of judges is important especially as the basis of the judge in handling cases. This attitude also fortifies the judge from despicable acts. Even though the judge's attitude was reflected and regulated in the provisions of the judge's code of ethics, however, the reality showed that the judge's attitude was far from expectations.Keywords: Pretrial - Determination of New Suspects - Judge Considerations